الإعاقة الحركية للرياضيين - رواب, عمار; مزاور, محمد; جاري, مراد (Tamayoz; No 04 (2018): مجلة التميز لعلوم الرياضة-مارس, 2019)
تعتبر الإعاقة الحركية نوع من أنواع الإعاقات التي يتعرض لها الإنسان في حياته ، وقد يولد بها الإنسان أو يتعرض لها من جراء مثير خارجي أخر ، حيث أن الإنسان المعاق حركيا سوف يكون لديه نقص تام أو جزئي في الحركة وذلك حسب درجة الإعاقة لديه ، ويعتبر ممارسة النشاط الرياضي للمعاقين حركيا مفيدا جدا لديهم من جميع النواحي،حيث تمثل الوسيلة المثلى والأفضل لسرعة عودة المعاق إلى مجتمعه وتألقه مرة أخرى ونجاحه كفرد منتج ضمن أفراد هذا المجتمع مندمجا فيه ومتفاعلا معه والرياضة عموما سواء للأصحاء أو المعاقين هي أحسن وسيلة للاحتفاظ باللياقة والصحة والقدرة على أداء العمل بكفاءة عالية . Abstract A motor disability is a type of disability that a person is exposed to in his or her life. The person may be born or exposed to it by another external stimulant. The disabled person will have a complete or partial disability in the movement according to the degree of disability. The athlete for the disabled is very useful in all aspects. It represents the best and best way to speed the return of the disabled to his society and his success once again and his success as a productive individual within the society, integrated with him and interacting with him and sports in general, whether for the healthy or the disabled is the best way to maintain fitness, health and ability to perform the Works with high efficiency.